Validation of aerosol measurements by the satellite sensors SAM II and Sage - Russell, P. B.; Mccormick, M. P.; Swissler, T. J. (1982)
A global data base on stratospheric aerosols has been obtained with the aid of the sensors SAM II and SAGE since the satellites carrying the sensors were launched in October 1978 and Feburary 1979, respectively. Several major comparative experiments have been conducted to acquire correlative data for validating the extinction profiles measured by these satellite sensors. The present investigation has the objective to present results from the first two of these experiments, which were conducted at Sondrestorm, Greenland, in November 1978, and at Poker Flat, Alaska, in July 1979. In both experiments, extinction profiles derived from the correlative sensors (dustsonde, lidar, filter, wire impactor) agreed, to within their respective uncertainties, with the extinction profiles measured by SAM II and SAGE (which in turn agreed with each other).